"The Infanta will marry the person who provides the Peace or the one who gives us the means to continue the War":1 The negotiations for the marriage between Infanta María Teresa of Austria and Emperor Leopold I (16541657). Issue 1 (2016) - López, Rocío Martínez
No abstract available